2014
DOI: 10.1016/j.kjms.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Macular asymmetry analysis in sighting ocular dominance

Abstract: Sighting ocular dominance is the preference of one eye over the other in terms of sighting. In this study, our aim was to examine differences in interocular and intraocular macular thickness, interocular fovea-optic disc angle, and foveal blood vessel asymmetries associated with sighting ocular dominance. Ninety eyes of 45 healthy young adults were included in this prospective, cross-sectional, and comparative study. Sighting ocular dominance was determined by a hole-in-the-card test. Macular thickness measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…However, ocular dominance is not associated with interocular macula thickness asymmetry (Pekel et al, 2014), but possibly associated with macular GC-IPL thickness (Choi et al, 2016) and RNFL thickness (Choi et al, 2014), although the preponderance for right-sided dominance (in common with motor dominance) is a confounding issue. In fact, work from animal models suggests ocular dominance is a property of the visual cortex, rather than the anterior visual pathway, with recent MRI techniques suggesting this may be true for humans also (Jensen et al,Commented [ET5]: It would be nice, for consistency, to go back to the question you asked in the abstract (when are the two eyes "importantly different"? )…”
Section: Discussionmentioning
confidence: 97%
“…However, ocular dominance is not associated with interocular macula thickness asymmetry (Pekel et al, 2014), but possibly associated with macular GC-IPL thickness (Choi et al, 2016) and RNFL thickness (Choi et al, 2014), although the preponderance for right-sided dominance (in common with motor dominance) is a confounding issue. In fact, work from animal models suggests ocular dominance is a property of the visual cortex, rather than the anterior visual pathway, with recent MRI techniques suggesting this may be true for humans also (Jensen et al,Commented [ET5]: It would be nice, for consistency, to go back to the question you asked in the abstract (when are the two eyes "importantly different"? )…”
Section: Discussionmentioning
confidence: 97%
“…Mean disc-fovea angle was in the right eye 6.49 ± 3.25° and in the left eye 5.80 ± 3.29° without a statistically significant difference between both eyes ( P = 0.13). Pekel and associates included 90 eyes of 45 healthy individuals with a mean age of 27.3 ± 6.6 years into their study and found a mean disc-fovea angle of 5.24 ± 1.77° in dominant eyes and of 5.49 ± 2.58° in the nondominant eyes without a significant ( P = 0.51) between both [ 3 ]. Rohrschneider measured the disc-fovea angle in 104 healthy individuals with an age ranging between about 20 years and 80 years and found a mean value of 5.6 ± 3.3° [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pekel et al (2014) published a study on inter-ocular asymmetry regarding the OCT measurements (macular thickness, optic disc, fovea angle values, and foveal visible blood vessel count), taking into account the ocular dominance [ 34 ]. They hypothesized that the foveal area should be poorly vascularized in the dominant eye, making the light passage easier.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis did not prove to be true because the blood vessel count was similar between the two eyes. They concluded that there is no significant symmetry difference between eyes [ 34 ]. Our study is limited by the fact that we did not evaluate the eye dominance and therefore cannot assess the relationship between the dominant eye and the more affected eye.…”
Section: Discussionmentioning
confidence: 99%